Northeast Siberian ice wedges confirm Arctic winter warming over the past two millennia. - Opel, Thomas; Laepple, Thomas; Meyer, Hanno; Dereviagin, Alexander Yu; Wetterich, Sebastian (PANGAEA, 2017)
Arctic climate has experienced major changes over the past millennia that are not fully understood in terms of their controls and seasonality. Stable-data from ice wedges in permafrost provide unique information on past winter climate. Recently, an ice-wedge record from the Lena River Delta suggested for the first time that Siberian winter temperatures increased throughout the Holocene, contradicting most other Arctic paleoclimate reconstructions which are likely biased towards the summer. However, the representativeness of this single record and the spatial extent of its reconstructed winter warming signal is unclear. Here, we present a new winter temperature record based on paired stable oxygen (d18O) and radiocarbon age data spanning the last two millennia from the Oyogos Yar coast in northeast Siberia. The record confirms the long-term winter warming signal as well as the unprecedented temperature rise in recent decades. This confirmation demonstrates that winter warming over the last millennia is a coherent feature in the northeastern Siberian Arctic, supporting the hypothesis of an insolation-driven seasonal Holocene temperature evolution followed by a strong warming likely related to anthropogenic forcing.
(Table 1) Radiocarbon ages of organic remains in Oyogos Yar ice-wedge samples and corresponding δ¹⁸O values
Keywords: Age; Age, 14C AMS; Age, comment; Age, dated; Age, dated standard deviation; Age, error; AWI_PerDyn; Date/Time of event; HAND; Lena2007; Oy7-04-IW2; Oy7-11-IW1; Oy7-11-IW7; Oy7-RIW; Oyogos Yar, East Siberia, Russia; Permafrost Research (Periglacial Dynamics) @ AWI; Probability; recent ice wedges; Sample, optional label/labor no; Sample ID; Sampling by hand; Sampling on land; δ18O, water